The morphology and relationships of Youngina capensis Broom and Prolacerta broomi Parrington - Gow, Chris E (Bernard Price Institute for Palaeontological Research, 1975)
Comprehensive descriptions of the osteology of Youngina capensis Broom and Prolacerta broomi Parrington are presented. New details of the braincase of Proterosuchus fergusi Broom are given as these became necessary for comparative purposes. It is suggested that the initial radiation of sauropsid reptiles was a Permian event as yet poorly documented. The phylogenetic position of Youngina forward and backward in time cannot be narrowly defined, though certain characters seem specifically to preclude it from lizard ancestry. Prolacerta, on the basis of tooth implantation, braincase morphology and postcranial anatomy is shown to be closest to the proterosuchian thecodonts. It is very definitely not concerned with lizard origins, but would on available evidence seem to be a perfectly good ancestor for the middle Triassic forms Macrocnemus and Tanystropheus which latter must cease to be regarded as lizard ancestors. We have here a rather distinct reptilian lineage which branched off from common ancestral stock just prior to the advent of archosaurs.
Keywords: Thecodontia; South Africa; sauropsida